Career Alert Planning. Instructor Guide - Lankard, Bettina; Ohio State Univ., Columbus. National Center for Research in Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
This instructor's guide to the Career Alert Planning (CAP) program is one of 14 components (see note) of a set of individualized materials designed to help participants find out about themselves and about the kind of work for which they are suited. In this program, participants become acquainted with occupations that are representative of 10 basic job functions. They learn how these occupations relate to personal interests, abilities, skills, educational goals, experiences, and training. They consider the work conditions, salary, and employment outlook for each occupation. Finally, participants use this information to make decisions and plans about the careers they will pursue. This instructor's guide explains the goals and objectives of the CAP program, the organization of the materials, and implementation procedures. It takes the instructor on a "walk through" of the program process, with examples from the various Job Function Booklets of the program. Sections of the instructor's guide contain information on how the program can be used, the instructor's role, and supplementing the program. Exercises and learning activities are provided to use with students on the following topics: decision making, risk, recognizing values, changing values, work attitudes, and personal values. (KC)
Sponsoring Agency: Employment and Training Administration (DOL), Washington, DC. Office of Youth Programs.
Contract Number: DOL-99-0-2297-33-52.
ERIC Note: For related documents see CE 031 933-972.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Choice; Career Counseling; Career Development; Career Education; Career Exploration; Career Guidance; Career Planning; Decision Making; Individualized Instruction; Instructional Materials; Learning Activities; Learning Modules; Postsecondary Education; Programed Instructional Materials; Secondary Education; Self Evaluation (Individuals); Teaching Guides; Teaching Methods; Values Clarification; Work Attitudes; Career Alert Planning Program; Guides, Classroom -- Teacher; Guides, Non-Classroom.